Differences in Contraceptive Use Before and During the COVID-19 Pandemic at One of Community Health Center in Surabaya - Oktavianti, Anisa Dwi; Sofia Al Farizi; Sri Ratna Dwiningsih (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: The COVID-19 pandemic has caused limitations, one of which is contraceptive services. The impact of this pandemic is different in each region. In Indonesia, there was a decrease in family planning acceptors at the beginning of the pandemic and it is feared that there will be a baby boom after the pandemic. During the pandemic, Surabaya was one of the areas with high COVID-19 cases. However, contrary to existing concerns, the number of pregnancies in Surabaya has actually decreased during 2020 (during the pandemic). One of the contraceptive health services in this area is at Jagir Community Health Center. Objectives: This study aims to determine the differences in contraceptive use before and during the COVID-19 pandemic at Jagir Community Health Center. Methods: This research method is quantitative through an observational analytic design.The sample size was 269 acceptors with a sampling technique using total sample method from family planning acceptors at the Jagir Health Center for the period March 2019 - February 2021 which included inclusion criteria. Data collection using medical records. Results: The results showed that the majority of acceptors before and during the pandemic were 20-35 years old with parity ≤ 2. Based on the chi-square test, the difference in contraceptive use before and during the COVID-19 pandemic (p-value <0.05), where during the pandemic there was a decrease in non-MKJP acceptors and an increase in MKJP acceptors. Conclusions: There is a significant difference in contraceptive use before and during the COVID-19 pandemic at Jagir Community Health Center.